The Students’ Feedback on WWW-course ”Electricity, Electronics and Environment” - Vesapuisto, M.; Vekara, T.; Korpinen, L.; Koskiranta, M.; Lehtelä, R. (Elektronika ir Elektrotechnika, 2010)
The aim of this paper is to compare between genders the students’ feedback on the web course Electricity, Electronics and Environment for the senior secondary school. Also, the exam results were analyzed according to gender. The course has been realized three times; in 2005 and twice in 2006. As a conclusion of the feedback and the exam results it can be stated that the girls did very well on the course. Their feedback was not as favorable as the boys’ but nevertheless they thrived in the exam. Boys are seemingly more interested in the usage and operation of electrical appliances than girls, but also clearly technical subjects – like the electric systems – seem to interest girls.